PENGARUH STRUKTUR MODAL, RISIKO BISNIS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Sektor Teknologi yang terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Salsa Fira; Endang Asliana; Endah Yuni Puspitasari (Worksheet : Jurnal Akuntansi, 2026)
The rapid growth of technology sector companies in Indonesia, accompanied by significant stock price fluctuations, indicates inconsistencies in firm value assessment influenced by financial performance and funding decisions. This study aims to analyze the effect of capital structure, business risk, and profitability on firm value in technology sector companies listed on the Bursa Efek Indonesia during the 2021–2024 period. The research applies a quantitative approach using secondary data obtained from published annual financial statements. The sampling technique employed purposive sampling based on predetermined criteria. Data analysis was conducted using multiple linear regression, preceded by descriptive statistical tests, classical assumption tests, and hypothesis testing. Firm value was measured using Price to Book Value (PBV), capital structure was proxied by Debt to Asset Ratio (DAR) and Long-Term Debt to Equity Ratio (LTDER), business risk was measured using Degree of Operating Leverage (DOL), and profitability was proxied by Return on Assets (ROA). The results indicate that capital structure and profitability have a significant effect on firm value, while business risk shows a varying influence depending on the company’s financial condition. These findings imply that optimal debt management and the ability to generate profits are essential factors in enhancing firm value, whereas excessive business risk may reduce investor confidence. Therefore, companies are expected to determine an optimal capital structure and maintain stable profitability to maximize firm value and attract potential investors.